Seasonal changes of serum 25-hydroxyvitamin D and intact parathyroid hormone levels in a normal Japanese population - Ono, Yasunaga; Suzuki, Atsushi; Kotake, Motoko; Zhang, Xiaoli; Nishiwaki-Yasuda, Keiko; Ishiwata, Yoko; Imamura, Shigeo; Nagata, Mutsuko; Takamoto, Satoru; Itoh, Mitsuyasu (Journal of bone and mineral metabolism, 2005)
We conducted an observational study in order to assess the prevalence of hypovitaminosis D and its seasonal changes, in the Tokai area (N35.3 E137.0), in 197 normal subjects in Japan. The mean serum 25-hydroxyvitamin D (25-OHD) level measured by direct radioimmunoassay (RIA) was lowest at the end of winter, and highest at the end of summer (15.1+/-7.1 ng/ml in March; 21.5+/-5.5 ng/ml in June; 31.6+/-5.6 ng/ml in September; 23.1+/-5.3 ng/ml in December; mean+/-SD). The prevalence of hypovitaminosis D (<20 ng/ml) was 86.7%, 33.4%, 1.0%, and 26.0% in March, June, September, and December, respectively. Mean plasma intact parathyroid hormone (iPTH) concentration was lowest at the end of summer and highest at the end of winter (28.2+/-9.3 pg/ml in March; 21.7+/-7.0 pg/ml in June; 19.8+/-6.9 pg/ml in September; and 25.7+/-9.2 pg/ml in December; mean+/-SD). Serum 25-OHD was inversely associated with iPTH (coefficient, -0.223; r=0.251; P<0.001). Serum 25-OHD levels were higher in men than in women. The serum 25-OHD level was positively associated with age, body weight, and body mass index, but not with body fat content. These results suggest a high prevalence of hypovitaminosis D associated with elevation of iPTH in Japan, in winter, even in a sunny area.